Reseña de Varela y Álvarez-Uría (Eds.) (2019). Conversaciones con Robert Castel - Gordo López, Angel (Athenea Digital. Revista de pensamiento e investigación social, 2019)
Reseña de Varela y Álvarez-Uría (Eds.) (2019). Conversaciones con Robert Castel